Algorithm for Recognizing the Type of Modulation and Measuring Parameters of Radar Signals with Chirp - D. V. Arkhipenkov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2022)
One of the most informative parameters of the signal of radar signals is its carrier frequency. Measuring and memorizing the carrier frequency of a reconnaissance radio-electronic device is one of the most important functions of a radio intelligence station, radio monitoring. Using the concept of an analytical signal, any signal can be represented through an envelope and phase, or quadrature components, which makes it possible to calculate the instantaneous frequency. The purpose of the work is to determine the effectiveness of the instantaneous frequency calculation method based on direct conversion in the time domain using several differentiators for measuring the time and frequency parameters of a chirp signal. The developed algorithm makes it possible to measure such parameters of the signal with chirp as steepness, pulse duration, repetition period, central frequency, spectrum width. This paper presents the implementation of an algorithm for measuring the instantaneous frequency with augmented double differentiation. The first differentiation allows you to measure the steepness of the signal as a sample average, the second differentiation – time points (pulse duration, repetition period). The signs of signal portraits are presented for a symmetrical, asymmetric signal with chirp, as well as in the absence of intra-pulse modulation. The simulation results showed that with the ratio of the sampling frequency to the signal band equal to 2.3, the error in measuring the steepness of the signal is 25 %, and at 11 – 8.8 %; the simulation results were carried out with a signal-to-noise ratio of 10 dB.